2009
DOI: 10.1007/s11255-009-9634-x
|View full text |Cite
|
Sign up to set email alerts
|

Statins and vitamin D: a friendly association in pre-dialysis patients

Abstract: The increased mortality rate observed in patients with chronic kidney disease is related to the high prevalence of cardiovascular disease in this population. Recently, it has been shown that interventional therapy with statins and/or vitamin D could improve the outcomes of these patients. The aim of this study was to identify the risk factors for mortality in a group of patients with chronic kidney disease (stages 4 and 5--pre-dialysis) and verify whether vitamin D and statins could change the outcome. We incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…The Prospective Pravastatin Pooling Project that included three studies has shown that pravastatin reduced significantly the CV composite outcome only in patients with moderate renal insufficiency [49]. We also found in an observational study that statins plus vitamin D reduced cardiovascular mortality in predialysis patients [50]. The SHARP trial also demonstrated the benefit of simvastatin plus ezetimibe in predialysis but not in patients already on dialysis [51].…”
Section: Dyslipidemiasupporting
confidence: 56%
“…The Prospective Pravastatin Pooling Project that included three studies has shown that pravastatin reduced significantly the CV composite outcome only in patients with moderate renal insufficiency [49]. We also found in an observational study that statins plus vitamin D reduced cardiovascular mortality in predialysis patients [50]. The SHARP trial also demonstrated the benefit of simvastatin plus ezetimibe in predialysis but not in patients already on dialysis [51].…”
Section: Dyslipidemiasupporting
confidence: 56%
“…Pravastatin also reduced significantly the incidence of myocardial infarction, coronary death, and coronary revascularisation by 23%, only in patients with moderate renal insufficiency [33]. Recently, we also could find, in an observational study, that statins plus vitamin D reduced cardiovascular mortality in predialysis patients (stages 4 and 5) [34]. …”
Section: Does the Use Of Statins Lower Cardiovascular Disease Burdmentioning
confidence: 99%
“…[1][2][3][4][5][49][50][51] Interestingly, some study results suggest that statins may increase 25D levels, which in turn may enhance beneficial effects of statin therapy. 4,52,53 Vitamin D may also have a role in the pathogenesis of vascular diseases because arterial vessel cells are target cells for vitamin D. 54 Effects of antiatherosclerotic vitamin D include (1) inhibition of macrophage to foam cell formation;…”
Section: Vitamin D and Risk Factors For Heart Diseasementioning
confidence: 99%